Future-Ready Finance: Building AI and Machine Learning Competencies among Financial Professionals - Malepati, Venkataramanaiah; Gowri, C. Mangala; Ranganatham, G.; Suneetha, B. (Nepalese Journal of Management Science and Research, 2026)
The rapid advancement of Artificial Intelligence (AI) and Machine Learning (ML) is redefining the skill requirements for finance professionals worldwide. This research article explores how the financial sector – including banking, investment management, fintech, and auditing – is developing AI/ML competencies to remain future-ready. Using a qualitative approach, we draw on contemporary case studies, expert interviews, and theoretical analysis to examine global trends, with particular emphasis on India. We review scholarly literature and industry reports to map the current landscape of AI/ML adoption in finance and the corresponding workforce upskilling initiatives. Key findings indicate a significant skills gap: According to a survey by the CFA Institute, only 3% of investment professionals report being proficient in artificial intelligence and machine learning concepts, despite growing interest and adoption in the sector (CFA, 2023). Case studies of banks and Big Four accounting firms illustrate proactive strategies such as in-house AI academies and large-scale training programs to build relevant expertise. Experts emphasise that developing AI/ML competencies involves not only technical training (e.g., data analytics, programming) but also strengthening soft skills such as critical thinking and adaptability to work effectively alongside intelligent systems. The discussion highlights global best practices and contextualises them for the Indian financial industry, which is poised to benefit from its large tech talent pool if upskilling challenges are addressed. We identify gaps in existing efforts and propose objectives for organisations and policymakers to cultivate an AI-ready financial workforce. In conclusion, being “future-ready” in finance will require continuous learning and strategic investment in human capital, ensuring professionals can leverage AI and ML ethically and efficiently to drive innovation in the financial services sector. This study provides a roadmap to integrate AI/ML into financial functions by investing in workforce upskilling, embedding analytics into decision-making processes, and driving organisational agility in an increasingly data-driven environment.